The starving heart. (4th February 2022) - Scheggi, V; Vanni, F; Filardo, C; Rinaldi, A; D"anna, G; Giammetti, S; Castellini, G; Alterini, B; Marchionni, N; Ricca, V
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Anorexia Nervosa (AN) is a psychiatric disorder that can lead to cardiac complications, especially in severely malnourished patients. Cardiovascular involvement includes autonomic dysfunction (increased vagal tone, bradycardia, orthostatic hypotension, syncope), arrhythmias, pericardial effusion, heart failure and sudden death. A few studies have examined the echocardiographic abnormalities secondary to AN, reporting mainly a decreased cardiac mass and an increased incidence of pericardial effusion. No previous studies examined the changes of Global Longitudinal Strain (GLS), which has been shown to be an early marker of myocardial damage in other subsets. Purpose: This study aimed to characterize echocardiographic abnormalities in AN, and to assess impairment of global and regional longitudinal strain (LS) and its clinical value in this context. Methods: We prospectively enrolled 42 consecutive patients (1 male) admitted to a highly specialized AN unit between November 2020 and July 2021 with AN (Mental Disorders, 4th Edition-DSM IVr). We also selected 34 healthy controls, matched for age and sex. In all subjects, we reported the cardiac frequency, systolic and diastolic blood pressure, blood examinations, and we performed an echocardiography, including GLS measurement. Eighteen patients were treated with enteral or parenteral feeding. A subset of 26 AN patients performed a second echocardiography after one month of follow up; 14 of them received forced feeding. Results: Compared with healthy subjects, AN patients had significantly lower albumin levels (45.1 ± 10.3 vs 66.0 ± 4.8 mg/dl, p = 0.031), lower FT3 levels (3.7 ± 1.0 vs 7.9 ± 6.4 pg/mL, p = 0.001), higher FT4 levels (13.8 ± 1.8 vs 9.6 ± 8.1 pg/mL, p = 0.008), a lower cardiac frequency (63 ± 18 vs 73 ± 12 bpm, p = 0.004), a higher incidence of pericardial effusion (9/42 vs 0/34, p = 0.008), a lower myocardial mass (62.3 ± 15.0 vs 98.5 ± 28.5 g, p < 0.001), a lower absolute value of GLS (-18.8 ± 2.8 vs -20.3 ± 2.0 %, p = 0.014) and basal LS (-15.4 ± 6.1 vs -19.6 ± 2.8 %, p < 0.001). The bull's eye mapping showed a plot pattern with blue basal areas in 17/42 AN patients vs 1/34 healthy subjects (p < 0.001). The 17 anorexic patients with a blue basal pattern needed forced feeding in a higher proportion (11/17 vs 7/25, p = 0.018) and presented more frequently amenorrhea (14/17 vs 11/25, p = 0.046). During the follow up (26 AN patients performed a second echocardiography), of 13 patients with blue areas in the first bull's eye mapping, 11 recovered a completely red pattern, and of 13 patients with a red bull's eye in the first examination, no one presented blue areas on the second one. Conclusions: GLS is significantly altered in AN patients and a basal blue pattern on bull's eye mapping individuates more severe cases. These changes seem to be reversible (Figure 1), although further studies are necessary to understand which factors influence this pattern besides BMI.